Réponses

2013-11-03T17:34:20+01:00
(x-4)(x+6)
x²+6x-4x-24
x²+2x-24
(a-5)(2a-7)
2a²-7a-10a+35
2a²-17a+35
(4-x²)(x+3)
4x+12-x³-3x²
(3x-2)(5x+1)
15x²+3x-10x-2
15x²-7x-2
(4-2x)(-1-3x)
-4-12x+2x+6x²
6x²-10x-4
(x+3)(x+3)
x²+3x+3x+9
x²+6x+9
(2-x)(2-x)
4-2x-2x+x²
x²-4x+4
(a+b)(a-b)
a²-ab+ab-b²
a²-b²
(x+6)²
x²+12x+36

Meilleure réponse !
2013-11-03T17:55:32+01:00
B=(x-4)(x+6)
  =x*x+x*6-4*x-4*6
  =x²+2x-24

C=(a-5)(2a-7)
  =a*2a-a*7-5*2a-5*(-7)
  =2a²-17a+35

D=(4-x²)(x+3)
  =4*x+4*3-x²*x-x²*3
  =x(au cube)+3x²+4x+12

E=(3x-2)(5x+1)
  =3x*5x+3x*1-2*5x-2*1
  =15x²-7x-2

F=(4-2x)(-1-3x)
  =4*(-1)+4*(-3x)-2x*(-1)-2x*(-3x)
  =6x²-14x-4

G=(x+3)(x+3)
  =x*x+x*3+x*3+3*3
  =x²+6x+9

H=(2-x)(2-x)
  =2*2+2*(-x)-x*2-x*(-x)
  =2-4x+x²